2017
DOI: 10.1002/ece3.3659
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soil respiration to soil management changes in an agropastoral ecotone in Inner Mongolia, China

Abstract: Studying the responses of soil respiration (R s) to soil management changes is critical for enhancing our understanding of the global carbon cycle and has practical implications for grassland management. Therefore, the objectives of this study were (1) quantify daily and seasonal patterns of R s, (2) evaluate the influence of abiotic factors on R s, and (3) detect the effects of soil management changes on R s. We hypothesized that (1) most of daily and seasonal variation in R s could be explained by soil tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 50 publications
(79 reference statements)
0
11
0
Order By: Relevance
“…3a). An earlier study (Xue and Tang 2018) reported an increase of 29% in the S R during the conversion of free grazing grassland into cropland in a semi-arid agropastoral ecotone in North China and suggested that soil management activities, mainly tillage and fertilizer input, decrease the level and storage of S C and that the soil aeration enhances S MA and SOM decomposition in cropland. In this study, the S C and S N varied significantly among all land use sites and decreased by 76-82% in the AF and 52-64% in the VF compared with the PFC and MFC (Fig.…”
Section: Soil Respiration In Different Land Usesmentioning
confidence: 98%
“…3a). An earlier study (Xue and Tang 2018) reported an increase of 29% in the S R during the conversion of free grazing grassland into cropland in a semi-arid agropastoral ecotone in North China and suggested that soil management activities, mainly tillage and fertilizer input, decrease the level and storage of S C and that the soil aeration enhances S MA and SOM decomposition in cropland. In this study, the S C and S N varied significantly among all land use sites and decreased by 76-82% in the AF and 52-64% in the VF compared with the PFC and MFC (Fig.…”
Section: Soil Respiration In Different Land Usesmentioning
confidence: 98%
“…Numerous studies have shown that R S rates typically increase over the course of short-term soil warming experiments (Gonzalez-Meler et al, 2017; Xue & Tang, 2018; Zhao et al, 2018) and long-term warming experiments (Noh et al, 2016; Zhou et al, 2016) and likely due to the promotion of soil microbial activity and a lack of restrictions on soil organic matter during warming treatment periods. Some studies also report that warming decreases R S levels during long-term warming experiments (Melillo et al, 2002; Marañón Jiménez et al, 2017; García-Palacios et al, 2018) and mainly due to the excessive consumption of carbon pools.…”
Section: Introductionmentioning
confidence: 99%
“…This result indicated that grazing had a significant impact on Rs in a temperate typical steppe that was not only inhibitory, thus contradicting our first hypothesis that grazing inhibited Rs. Similarly, a study conducted under different land uses in Inner Mongolia reported that the average Rs during the growing season was 1.43 ± 0.04 μmol·m −2 ·s −1 for free grazing (only during the growing season with nine sheep ha −1 ) and 1.37 ± 0.03 μmol·m −2 ·s −1 for enclosed grassland grazing (Xue & Tang, 2018). In contrast to the findings of the study, the higher Rs observed under rest-rotation grazing system in our study was likely due to the lower grazing intensity (2–4.5 vs 9 sheep ha −1 ).…”
Section: Discussionmentioning
confidence: 92%